Non-linear evolution of large waves in deep water – the influence of directional spreading and spectral bandwidth - Adcock, T; Taylor, P (International Society of Offshore and Polar Engineers (ISOPE), 2016)
As large waves form in the open ocean their dynamics are modified from classic linear dispersion by non-linear physics. In this study we use a numerical model to study the evolution of isolated wave-groups in deep water. We find that the non-linear changes are rather sensitive to the initial conditions, with small changes in parameters such as directional spreading giving significantly different results. In all cases, although as aforementioned in differing degrees, we find changes to the shape of the extreme wavegroup – the wave-groups contracting in the mean wave direction, expanding laterally to increase the width of the extreme crest, and with the largest wave moving to the front of the groups. We find that significant extra elevation of the wave-group only occurs for cases which are close to uni-directional.